THE ROLE OF GOVERNMENT IN THE DEVELOPMENT OF INNOVATIVE ACTIVITY IN THE REPUBLIC OF KAZAKHSTAN (Journal of Economic Research & Business Administration, 2018)
The course of industrial and innovative development of Kazakhstan, laid in the beginning of 2000,strategically correctly identified the main risks and priority directions for the development of the economyof Kazakhstan: a non-alternative course was chosen to diversify, increase the competitiveness of theeconomy through innovation and avoid dependence on raw materials. As analysis of innovative developmentin the Republic of Kazakhstan shows, innovative activity in the country plays a large role, but sofar it is not the main factor of increasing the country’s competitiveness in the world market.In the conditions of building an innovation system, an economy based on knowledge, the only truedevelopment strategy is the intensification of innovation potential. The country’s innovation potentiallies in the formation and formation of an educated nation, the compilation and integration of varioustypes of sources, such as material, financial, intellectual and other. The most important factor in thegrowth of the innovation economy is the country’s intellectual potential.This article examines the issues of state regulation of innovation activities, including the features ofthe formation of an effective mechanism for financing innovation and the development of intellectualcapital. Constant and continuous creation and implementation of innovations is the main factor of prosperityin the competitive struggle of any enterprise, region and country as a whole.The purpose of the research: to study the influence of the role of the state on the country’s innovativedevelopment; analysis of various applied complex and multilevel approaches on the part of the stateto manage innovation activities; Identification of the most effective tools and mechanisms stimulatinginnovation activity.Research methods: general scientific (synthesis, deduction, induction, generalization, testing, survey,observation, forecasting, scientific abstraction, statistical analysis, logical), as well as methods ofgrouping and classification, expert evaluation. Results: the increasing role of the state as the most importantregulator and stimulator of positive activity and social responsibility of private innovation businessis defined. Creation of a favorable innovation climate is becoming the most important direction of stateregulation in the innovation sphere, and such instruments as regulatory legal acts and economic incentivesthat contribute to improving the quality of innovations, reducing the costs of their implementationand increasing the socio-economic returns from innovations create conditions for the mass distributionof various innovative forms in the country. Scientific novelty: it is revealed that in order to strengthen thecompetitive positions of innovative business, the state should promote the formation and developmentof public and private partnerships in innovation activities. Also, the creation of an entire system, wherethe spheres of application of intellectual, creative work of people: science, education, culture should beput at the forefront, can also be an increase in innovative activity.